Telephone consultations for skin cancers during COVID-19. Issue 1 (January 2022) - Coll, Yasmine; Elmahgoub, Fatima; Currie, Roger
Abstract : Introduction: Within Crosshouse hospital, as a result of COVID19, we are trying to limit footfall by managing patients over telephone, if deemed appropriate. It was highlighted that referrals from allied HCPsfor urgent/non-urgent skin lesions may fall under the category of consultations which could be carried out by DCTs over telephone, in order to reduce the number of visits required for each patient. Methods: A questionnaire was completed by fellow DCT colleagues to assess how comfortable they are at ensuring all the required information is obtained during telephone consultations, and if they felt there was any way the consistency and quality of these could be improved. Results: Our fellow DCT colleagues expressed that they had had little training with regards to skin cancers in previous posts and felt that by carrying out teaching on relevant topics their confidence would be increased. With regards to improving the consistency of consultations, it was highlighted that a proforma would be beneficial. Conclusions: Following intervention; a further questionnaire was distributed which showed that by inclusion of these teaching topics, as well as a structured proforma, confidence had improved greatly. This also ensures that patients are receiving the best possible care during the COVID19 pandemic, and cancer patients can continue to be listed for procedures in a more streamlined approach. Although this transition during the COVID-19 period creates opportunities for flexibility, it also highlights important training needs that will need consideration as the impact of this pandemic on health services may continue for years.